Neotectonic structure of the Argolic Gulf - Papanikolaou, D.; Chronis, G.; Metaxas, Ch. (Bull. Soc. Geol. Greece, 1994)
Seismic and bathymetric profiles within the Argolic Gulf permitted the study of its neotectonic structure. The morphological data were analysed in the form of a morphological mean slope map on which the morphological discontinuities and the planar surfaces were distinguished. The neotectonic structure of the gulf is mainly created by the following fault sets grouped:(i) in two NW-SE zones of major border normal faults, separating the alpine basement from the sedimentary fill of the basin,(ii) in several E-W transcurrent faults which create horizontally escaping neotectonic blocks and,(iii) normal faults, some of which probably with oblique-slip motion, forming minor neotectonic blocks especially within the continental platform.The overall geomorphological and neotectonic structure and other characteristics of the post-alpine sedimentation show an asymmetry with more intence phenomena along the western margin of the gulf. The continental platform is highly fractured and Holocene vertical block movements of the order of 20 - 30 m are detected.
Keywords: Argolikos Gulf, Neotectonic, morphotectonic analysis, normal fault, Holocene,